(untitled) (Bangladesh Journal of Medical Science, 2017)
Head trauma can lead to hearing loss. Both sensorineural and conductive hearing loss has been reported in cases of head injury. We report a case of labyrinthine concussion and subdural hematoma in the opposite ear of a patient who had head trauma after involved in motor vehicle accident. A complete hearing assessment for head trauma patients should be advised as it can avoid misdiagnosis and negligence in management. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.594-596